Bulk and Single-Nucleus Transcriptomics Highlight Intra-Telencephalic and Somatostatin Neurons in Alzheimer’s Disease - Consens, Micaela E.; Chen, Yuxiao; Menon, Vilas; Wang, Yanling; Schneider, Julie A.; De Jager, Philip L.; Bennett, David A.; Tripathy, Shreejoy J.; Felsky, Daniel (Frontiers in Molecular Neuroscience, 2022)
Cortical neuron loss is a pathological hallmark of late-onset Alzheimer’s disease (AD). However, it remains unclear which neuronal subtypes beyond broad excitatory and inhibitory classes are most vulnerable. Here, we analyzed cell subtype proportion differences in AD compared to non-AD controls using 1037 postmortem brain samples from six neocortical regions. We identified the strongest associations of AD with fewer somatostatin (SST) inhibitory neurons (β=-0.48, pbonf=8.98x10-9) and intra-telencephalic (IT) excitatory neurons (β=-0.45, pbonf =4.32x10-7). Replication in three AD case-control single-nucleus RNAseq datasets most strongly supported the bulk tissue association of fewer SST neurons in AD. In depth analyses of cell type proportions with specific AD-related neuropathological and cognitive phenotypes revealed fewer SST neurons with greater brain-wide postmortem tau and beta amyloid, as well as a faster rate of antemortem cognitive decline. In contrast, IT neuron proportions were associated with improved cognition and residual cognition - a measure of cognitive resilience - but not canonical AD neuropathology. Our findings implicate somatostatin inhibitory and intra-telencephalic excitatory neuron subclasses in the pathogenesis of AD and in cognitive resilience to AD pathology, respectively.